Ignition of a vacuum arc discharge in plasma sources by non-traditional methods - Iurii Sysoiev; Yurii Shyrokyi; Andrey Sysoiev (Авіаційно-космічна техніка та технологія, 2022)
The subject of research in this article is the processes of excitation of a vacuum-arc discharge in plasma sources by unconventional methods: the transition of a glow discharge into an arc discharge (TGA) and arc initiation using laser radiation (LR). The goals are to increase the service life of ignition systems (IS) for plasma sources to expand their technological capabilities and the quality of the resulting coatings. The tasks: to investigate the modes in which non-traditional IS stably excite an arc discharge and ensure their high service life. The methods used are analytical and experimental research methods, which were carried out using the developed new devices. The following results have been obtained. The study of arc excitation using a TGA in a system of Penning-type electrodes showed that the use of a plasma source with such an IS is advisable in processes in which reaction gases are used to form compounds with its material on the cathode surface. Otherwise, after several hundred triggering, the probability of PTD decreases to values of 10...50 %, which is explained by the cleaning of the cathode surface from various inhomogeneities. The ignition of the TGA arc using dielectric stimulators of the cathode spot (CS) expands the technological capabilities of the plasma source. Here, the arc discharge stably ignites in the pressure range from 10-2 to 10 Pa, with voltage pulses of the order of 2 kV in a magnetic field with a strength of 5.6 104 A/m and a starting pulse energy of 2 J. The design of a plasma source with a combined IS has been developed, which makes it possible to achieve the maximum reliability of the excitation of a vacuum arc. A plasma source with a combined IS has a reliability of starting the device in the pressure range of 10-2 ... 5 Pa, the presence of a magnetic field of 104 ... 105 A/m and amplitude of starting pulses of 1.5...2.0 kV close to 100%. The conditions under which the formation of vapor condensate of the plasma source cathode material on the surface of the LR input window does not occur are considered, and it is proposed to solve this problem by supplying energy to the condensation zone directly to the formed condensate layer. Conclusions. The use of non-traditional methods of excitation of a vacuum-arc discharge was substantiated and studied: using TGA and LR, a combined IS was developed, in which traditional and non-traditional methods of arc ignition are combined using the advantages of each method, parameters were found under which the IS work under study reliably and have high resource.